2015
DOI: 10.1021/acsami.5b08773
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of Metal–Organic Framework Copper(II) Benzene-1,3,5-tricarboxylate (CuBTC) onto Cotton Fabric as a Nitric Oxide Release Catalyst

Abstract: Immobilization of metal-organic frameworks (MOFs) onto flexible polymeric substrates as secondary supports expands the versatility of MOFs for surface coatings for the development of functional materials. In this work, we demonstrate the deposition of copper(II) benzene-1,3,5-tricarboxylate (CuBTC) crystals directly onto the surface of carboxyl-functionalized cotton capable of generating the therapeutic bioagent nitric oxide (NO) from endogenous sources. Characterization of the CuBTC-cotton material by XRD, AT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(90 citation statements)
references
References 62 publications
2
81
0
Order By: Relevance
“…This property has led to the exploitation of copper‐based MOFs for the design of NO‐generating films, as reported recently by Neufeld et al 128, 129, 130. The films were fabricated by doping water‐soluble copper‐based MOFs to a range of materials (chitosan, poly(vinyl chloride), cotton fabric).…”
Section: No Delivery Via Catalytic Approachesmentioning
confidence: 95%
“…This property has led to the exploitation of copper‐based MOFs for the design of NO‐generating films, as reported recently by Neufeld et al 128, 129, 130. The films were fabricated by doping water‐soluble copper‐based MOFs to a range of materials (chitosan, poly(vinyl chloride), cotton fabric).…”
Section: No Delivery Via Catalytic Approachesmentioning
confidence: 95%
“…To improve the NO payload and stability, achieve targeted NO delivery through multi-functionalization and elongate NO releasing lifetime, many different scaffolds have been used as NO-releasing or NO-generating vehicles. These include micelles, 138,190,191 microbubbles, 192 proteins, 193197 liposomes, 126,198 inorganic nanoparticles (such as silica, 70,199203 gold, 204,205 microparticles, 198,206 zeolites, 207,208 ), metal-organic frameworks (MOFs), 209212 dendrimers, 71,213,214 xerogels, 215217 electrospun fibers, 88,100,218 natural polymers (chitosan, 8587,219221 gelatin, 222 etc. ), and other organic polymers (polymethacrylate, 223 polyester, 224,225 polydimethylsiloxane (PDMS), 226 polysaccharides, 227,228 hydrogel, 178,179,229,230 PVA, 49,231,232 polyurethanes, 161,162,233,234 and PVC 154 ).…”
Section: Polymer-based Strategies For No Deliverymentioning
confidence: 99%
“…210212 It has been reported that CuBTC can be extruded within Tecoflex SG80A polyurethane into single lumen tubing while maintaining the catalyst structure and functionality. The in vitro NO release generated from endogenous RSNO species ranges from 1 h to 16 h with tunable dosage, depending on the specific RSNO levels present in the soaking solution.…”
Section: Polymer-based Strategies For No Deliverymentioning
confidence: 99%
“…Prior research has demonstrated that Cu ions initiate NO release from both endogenous and synthetic RSNOs . To validate the role of released Cu ions in the catalytic activity of our Ti–Cu coatings, the samples were immersed in PBS for 30 min to provide a leach solution, and then the concentrations of NO generated by the leach solutions were measured by the Saville–Griess assay.…”
Section: Resultsmentioning
confidence: 99%
“…RSNOs can decompose to release NO in the presence of catalytic agents such as organoselenium, thiol groups, or Cu 2+ ions to improve their hemocompatibility. Copper ions catalyze and initiate NO release from both endogenous and synthetic RSNOs . NO can be effectively generated from RSNO through the catalytic activity of Cu ions as described by reactions (1–3) RSNO + 2OH= RS+ NO2 + normalH2O 2Cu2++ 2RS= 2Cu++ RSSR Cu++ RSNO = Cu2++ RS+ NO…”
Section: Introductionmentioning
confidence: 99%